Engaging and Empowering Malaysian Students Through Open and Distance Learning in the Post-COVID Era - Abdullah, Zaleha; Mohamad Said, Mohd Nihra Haruzuan (Frontiers in Education, 2022)
With the outbreak of COVID-19, online open and distance learning (ODL) has become increasingly relevant, particularly among those who aim to pursue postgraduate studies. ODL provides an opportunity for many to study while working or raising a family. Nevertheless, ODL programs are associated with low student engagement and high non-completion rates compared to traditional programs. Among the main contributing factors are communication and course design, which relate to the level of responsiveness of instructors and the quality of course design thus delivery through online. An innovative approach is needed to address these issues, and heutagogy seems to be a viable alternative. Nevertheless, the heutagogical approach alone is incomplete without considering the instructional scaffolding technique that can affect adult students’ engagement. This study introduces a model that combines heutagogy and instructional scaffolding (HEIS) as a guideline in conducting a fully online ODL course called Technology and Media Design. It interrogates the impact of the course design from the perspective of postgraduate students and instructors in one of Malaysia’s public universities. Recommendations include for faculties with ODL courses to continuously help develop instructors’ competencies and using more suitable assessment approaches e.g., project-based.